Saint Margaret Church, Circular Road, Belmont. - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, Trinidad, 2010)
Image depicts a view of the Saint Margaret Catholic Church. The church is located in the town of Belmont, on the outskirts of the capital city of Port of Spain, on the island of Trinidad, in the twin-island Republic of Trinidad and Tobago.
Colour: Shades of Red, Brown, Blue, Green and Gray; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Church buildings--Trinidad and Tobago; Buildings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Belmont; [1905]; Church architecture--Trinidad and Tobago; Architecture--Details; Towers--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Anglican church buildings--Trinidad and Tobago